Miniaturised robotic guide dog: for visually impaired travelling assistance - Ibrahim, Aisyah; Toha, Siti Fauziah; Idris, Ahmad Syahrin; Nordin, Nor Hidayati Diyana (Persatuan Saintis Muslim Malaysia (PERINTIS), 2023)
Visual impairment (VI) has gained increasing concern in the eyecare realm due to rising population in society globally. Over 1 billion are compelled to live with this condition simply because they cannot get the treatment and cure that they needed. Visual impairment, especially in developed countries, has serious implications. Its detrimental effects reduce the ability of individuals affected to work independently and can have a negative impact on personal and quality of life. The visually disabled person had to depend on another person whenever they had to walk around. This contributes to the lack of motivation to travel alone for the visually impaired person. Navigation plays a fundamental role amongst the activities that affected by visual impairment. Their ability to move independently in safety are restricted and difficult. The world has become more and more involved in supporting the disabled persons to improve their life by providing many healthcare systems. Even though there is modernized solution that exist nowadays but there are also disadvantages to that which are the possibility of poor connectivity, poor video performance in specific situations (like low-ambient light, high dynamic contrast scenes or motion blur) and the cost of training and employing guidance personnel. Thus, this book showcased the design of the miniaturised robotic device to help visually impaired in mobility by using ultrasonic sensor to detect obstacle and notifies the user using haptile feedback if there are obstacles that may lie ahead of the user’s path. This book also explores on the implementation of IoT into this miniaturized robot by pairing mobile phone to it for GPS tracking and navigate the user to arrive their destination safely.